Psychosocial and Pharmacological Management of Pain in Pediatric Sickle Cell Disease. Issue 2 (March 2014) - Hildenbrand, Aimee K.; Nicholls, Elizabeth G.; Daly, Brian P.; Marsac, Meghan L.; Tarazi, Reem; Raybagkar, Deepti
Abstract : : For children with sickle cell disease (SCD), pain is associated with significant current and future morbidity and mortality. Unfortunately, few evidence–based guidelines exist for the management of pain episodes in children with SCD. To inform empirically based treatment strategies for pain management in pediatric SCD, this review integrates and evaluates the extant literature on psychosocial and pharmacological approaches to the management of pain. Findings reveal a paucity of rigorous investigations of psychosocial and pharmacological pain management interventions in children with SCD. Psychosocial interventions included were primarily cognitive–behavioral in nature, whereas pharmacological approaches targeted non–opioid analgesics (ie, nonsteroidal anti–inflammatory drugs and corticosteroids) and opioid medications (ie, morphine and oxycodone). However, to date there is not a "gold standard" for pain management among children with SCD. Because psychosocial and physiological processes each play a role in the etiology and experience of pain, effective pain management requires multidimensional, comprehensive treatment approaches. Considering the significant impact of pain on functional outcomes and quality of life among children with SCD, additional clinical trials are warranted to ensure that interventions are safe and efficacious.